Influence of the dispersion medium on the properties of CdTe micro- and nanocrystals in a colloidal solution - Kapush, O.; Budzulyak, S.I.; Korbutyak, D.V.; Vakhnyak, N.D.; Boruk, S.D.; Dzhagan, V.M.; Yemets, A.I.; Valakh, M.Ya. (Functional Materials, 2019)
Surface and optical properties of CdTe nanoparticles obtained by grinding (40-150 nm, microcrystals) and colloidal synthesis (1-4 nm, nanocrystals) methods are investigated. It is shown that the most intensive adsorption of stabilizer molecules on the CdTe surface occurs when solvents are better wetting the surface of CdTe particles. It is found that the best stabilization of both the micro- and nanocrystals of CdTe is provided by using methyl and ethyl alcohol as the dispersion medium. The basic characteristics of photoluminescence of CdTe nanocrystals stabilized with thioglycolic acid in deionized water, methanol and ethanol of various concentrations are reported.